Pengaruh Riwayat Kesehatan Terhadap Kunjungan Antenatal Care di Klinik Salfa Medika Lebak Banten Tahun 2025 - Elfira Sri Futriani; Meneng Alinda Febriani (Jurnal Ners, 2025)
Pregnancy examination (ANC) is very important in achieving a healthy pregnancy. Through this examination, you can find out the progress of the pregnancy, the health level of the womb, the condition of the fetus, and detect diseases or abnormalities in the womb before they become complications. Incomplete pregnancy checks can increase the risk of death due to conditions that can be avoided or treated early. To determine the effect of health history on antenatal care visits at the Salfa Medika Clinic Lebak BantenThis research uses a quantitative descriptive research type with a cross sectional study approach, the sample in this study was 50 pregnant women, chi square statistical analysis test. There is an influence of health history on antenatal care visits with a value of p=0.025.Routine ANC examinations enable pregnant women to identify and manage pregnancy, childbirth and postpartum risks, thereby increasing the safety of mother and baby.